BOSHLANG‘ICH SINF O‘QUVCHILARIDA NUTQ MADANIYATINI RIVOJLANTIRISHNING AKSIOLOGIK YONDASHUVLARI (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article analyzes the axiological approaches to developing speech culture among primary school students. In the educational process, speech activity plays an important role not only in the development of linguistic competence but also in the formation of students’ moral and cultural values.The research examines the essence of speech culture, its structural components, and the axiological foundations of developing speech culture in primary education. Special attention is paid to the role of national and universal values in developing communicative competence among students.The results indicate that the application of axiological approaches in the educational process significantly contributes to the development of students’ speech culture, social communication skills, and moral values.